Good news, planet Earth! : what's being done to save our world, and what you can do too! - Bentley, Sam (DK Publishing, 2023)
Join sustainability enthusiast and climate activist Sam Bentley as he shares the hopeful developments combating climate change! Do you feel like climate change is just getting worse and there's nothing you can do to stop it? Good news--there are tons of efforts already underway to save our planet, and we'd love for you to join the fight. Good News, Planet Earth! is your go-to guide to learn all about the amazing sustainable developments that are happening worldwide to combat global warming, pollution, deforestation, the use of wasteful products, and threats to our diverse wildlife.